Psoriasis scoring and evaluation form- an innovative approach towards effective patient care - Pandey, Ajay; Swain, J. P. (International Journal of Advances in Medicine, 2017)
Psoriasis is one of the most common skin diseases which we encounter during our day to day practice.Increased awareness among people and easy availability of phototherapy units has increased the number of patients seeking treatment. Patients receiving phototherapy or immunosuppressive drugs are prone to develop side effects of these therapies, so it is important to have a careful watch on their laboratory parameters, therapeutic doses and adverse reactions like erythema reduction in blood counts.